Asia-Pacific Forest Sector Outlook: Innovative forestry for a sustainable future. Youth contributions from Asia and the Pacific - Pingault, N.; Roshetko, J.M.; Meybeck, A. (CGIAR Research Program on Forests, Trees and Agroforestry and Food and Agriculture Organization of the United Nations, 2021)
This publication assembles selected papers prepared by youth from the Asia-Pacific region on innovative forest technologies and their contribution to sustainable forestry and sustainable forest management. It is part of a roadmap on innovative forest technologies in the Asia-Pacific region developed by FAO and CIFOR, lead center of the CGIAR research programme on Forests, Trees and Agroforestry (FTA).